A comparative planning study of step-and-shoot IMRT versus helical tomotherapy for whole-pelvis irradiation in cervical cancer - Chitapanarux I. (Japan Radiation Research Society, 2015)
© 2015 The Author. The aim of this study was to compare the dosimetric parameters of whole-pelvis radiotherapy (WPRT) for cervical cancer between step-and-shoot IMRT (SaS-IMRT) and Helical Tomotherapy™ (HT). Retrospective analysis was performed on 20 cervical cancer patients who received WPRT in our center between January 2011 and January 2014. SaS-IMRT and HT treatment plans were generated for each patient. The dosimetric values for target coverage and organ-at-risk (OAR) sparing were compared according to the criteria of the International Commission on Radiation Units and Measurements 83 (ICRU 83) guidelines. Differences in beam-on time (BOT) were also compared. All the PTV dosimetric parameters (D5%, D50% and D95%) for the HT plan were (statistically significantly) of better quality than those for the SaS-IMRT plan (P-value < 0.001 in all respects). HT was also significantly more accurate than SaS-IMRT with respect to the D98% and Dmean of the CTV (P-values of 0.008 and <0.001, respectively). The median Conformity Index (CI) did not differ between the two plans (P-value = 0.057). However, the Uniformity Index for HT was significantly better than that for SaS-IMRT (P-value < 0.001). The median of D50% for the bladder, rectum and small bowel were significantly lower in HT planning than SaS-IMRT (P-value < 0.001). For D2%, we found that HT provided better sparing to the rectum and bladder (P-value < 0.001). However, the median of D2% for the small bowel was comparable for both plans. The median of Dmax of the head of the left femur was significantly lower in the HT plan, but this did not apply for the head of the right femur. BOT for HT was significantly shorter than for SaS-IMRT (P-value < 0.001). HT provided highly accurate plans, with more homogeneous PTV coverage and superior sparing of OARs than SaS-IMRT. In addition, HT enabled a shorter delivery time than SaS-IMRT.